2018
DOI: 10.1016/j.foodchem.2017.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Oral bioaccessibility of toxic and essential elements in raw and cooked commercial seafood species available in European markets

Abstract: The oral bioaccessibility of several essential and toxic elements was investigated in raw and cooked commercially available seafood species from European markets. Bioaccessibility varied between seafood species and elements. Methylmercury bioaccessibility varied between 10 (octopus) and 60% (monkfish). Arsenic (>64%) was the toxic element showing the highest bioaccessibility. Concerning essential elements bioaccessibility in raw seafood, selenium (73%) and iodine (71%) revealed the highest percentages. The bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 74 publications
7
25
0
2
Order By: Relevance
“…Also, Stévant et al (2018) reported decreased I content of S. latissima, to below 2,000 mg I/kg dw (originally 4,898 mg/kg dw in May 2015 and 6,568 mg/kg dw in June 2015), after a 1 hr soaking treatment in freshwater (32 • C). However, when compared to raw L. digitata, steaming it (5 min, 105 • C) resulted in an increased concentration of I (p < .05, n = 20; Alves et al, 2018). In another study, Nitschke and Stengel (2016) investigated the influence of processing on I content in A. esculenta (n = 5), Palmaria palmata (n = 4), and U. intestinalis (n = 5).…”
Section: 123mentioning
confidence: 99%
“…Also, Stévant et al (2018) reported decreased I content of S. latissima, to below 2,000 mg I/kg dw (originally 4,898 mg/kg dw in May 2015 and 6,568 mg/kg dw in June 2015), after a 1 hr soaking treatment in freshwater (32 • C). However, when compared to raw L. digitata, steaming it (5 min, 105 • C) resulted in an increased concentration of I (p < .05, n = 20; Alves et al, 2018). In another study, Nitschke and Stengel (2016) investigated the influence of processing on I content in A. esculenta (n = 5), Palmaria palmata (n = 4), and U. intestinalis (n = 5).…”
Section: 123mentioning
confidence: 99%
“…The mercury bioaccessibility ranged from 10% in octopus (Octopus vulgaris) to 60% in monkfish (Lophius piscatorius) [21]. Thus, although the mercury after different cooking methods is almost unchanged in the present study, the estimation of exposure of mercury can probably be overestimated due to a reduced bioaccessibility of the mercury after cooking [21]. However, this was not assessed in this experiment and must be explored further.…”
Section: Discussionmentioning
confidence: 67%
“…The iodine content per 100 g fillet was reduced due to increased dry weight and reduced weight of the cod fillet after boiling. Steaming (105 • C in aluminum foil for 15 min) has previously been shown to not affect iodine content in hake (Merlucius australis), monkfish (Lophius piscatorius), mackerel (Scomber scombrus), tuna (Katsuonus pelamis), plaice (Pleuronectes platessa), mussel (Mytilus edulis), octopus (Octopus vulgaris), and shrimp (Litopenaeus vannamel) [21]. In the study by Doh et al, 2019, they found more than 60% loss of iodine after boiling abalone (Haliotis discus hannai) and 32% reduction after steaming or grilling [22].…”
Section: Discussionmentioning
confidence: 99%
“…Consumer's guidelines are based on the assumption that MeHg from food is absolutely absorbed after human ingestion. However, it seems to overestimate the real assimilation of MeHg, since the nature of the matrix, fish species, cooking processes and the co-ingestion of certain food components seems to play a relevant role on the potential human assimilation of ingested Hg [113][114][115][116][117][118]. For example, cooking practices like, steaming, boiling, grill and frying have been evaluated [113,114,118,119], resulting in a reduction of the potential absorption at the intestinal epithelium level up to 90% [114], The co-ingestion of polyphenol-rich beverages like tea and coffee or pure polyphenols are leading to a decrease on Hg bioaccessibility [116,118,119].…”
Section: Discussionmentioning
confidence: 99%